Denning behaviour of the European badger (Meles meles) correlates with bovine tuberculosis infection status - Weber, Nicola (Behav Ecol Sociobiol, 2012)
Heterogeneities in behaviours of individuals may underpin important processes in evolutionary biology and ecology, including the spread of disease. Modelling approaches can sometimes fail to predict disease spread, which may partly be due to the number of unknown sources of variation in host behaviour. The European badger is a wildlife reservoir for bovine tuberculosis (bTB) in Britain and Ireland, and individual behaviour has been demonstrated to be an important factor in the spread of bTB among badgers and to cattle. Radio-telemetry devices were deployed on 40 badgers from eight groups to investigate patterns of den (sett) use in a high-density population, where each group had one or two main and three to eight outlier setts in their territory. Badgers were located at their setts for 28 days per season for 1 year to investigate how patterns differed between individuals. Denning behaviour may have a strong influence on contact patterns and the transmission of disease. We found significant heterogeneity, influenced by season, sex and age. Also, when controlling for these, bTB infection status interacting with season was highly correlated with sett use. Test-positive badgers spent more time away from their main sett than those that tested negative. We speculate that wider-ranging behaviour of test-positive animals may result in them contacting sources of infection more frequently and/or that their behaviour may be influenced by their disease status. Measures to control infectious diseases might be improved by targeting functional groups, specific areas or times of year that may contribute disproportionately to disease spread. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00265-012-1467-4) contains supplementary material, which is available to authorized users.